Design and Analysis of Main Drive Mechanism of the Helical Gear Shaping Machine with Adjustable Device - Xiong Xianwen; Cheng Weilin (Jixie chuandong)
Focusing on the existing problems in the domestic NC gear shaping machine,such as the manufacturing cost of helical guideway are expensive and replacement requires a fair of time and a lot of skills. The mechanical structure for realizing the synchronization between the additional rotation and generating motion is proposed based on the principle of helical gear shaping,an adjustable device is added in the existing NC shaping machine,which did not require the replacement of the helical guideway responds to the production of workpiece with different helical angles,the specific methods to achieve the additional rotation is discussed. The results show that the mechanism can meet the production of workpiece with different helical angles,the auxiliary time of shaping process is shortened,all of these can improve the efficiency and flexibility greatly.